Hypoglycemia Associated With Insulin Use During Treatment of Hyperkalemia Among Emergency Department Patients - Jacob, Bobby C. (Hosp Pharm, 2018)
Purpose: Hypoglycemia is a common adverse event associated with insulin during treatment of hyperkalemia in hospitalized patients; however, limited data exist regarding hypoglycemia incidence and appropriate dosing strategies for treatment of patients in the emergency department. The study objective was to determine the incidence of hypoglycemia associated with insulin use during treatment of hyperkalemia among patients seen in the emergency department. Methods: This was an Institutional Review Board (IRB)–approved retrospective, chart-review study. All adult patients who received intravenous regular insulin as a result of an order from the emergency department hyperkalemia order set were eligible for inclusion. The main clinical outcomes were incidence of hypoglycemia (blood glucose <70 mg/dL) and severe hypoglycemia (blood glucose <40 mg/dL). Blood glucose was checked within 24 hours of insulin administration. Results: A total of 172 patients were included. The incidence of hypoglycemia was 19.8% (n = 34) and the incidence of severe hypoglycemia was 5.2% (n = 9). Hypoglycemic patients had a significantly lower median blood glucose at baseline compared to those who did not develop hypoglycemia (83.5 [72.0-112.0] mg/dL vs 123.0 [96.0-167.0] mg/dL, P < .0001); however, no difference was noted between groups in the average insulin dose administered (0.11 ± 0.04 units/kg vs 0.12 ± 0.05 units/kg, P = .6175). Conclusion: There is a concerning risk of hypoglycemia associated with insulin use during treatment of hyperkalemia in the emergency department. Standard insulin doses may not be appropriate in some cases like patients with lower baseline blood glucose. Further research is warranted to develop safer hyperkalemia treatment protocols that mitigate this high risk of hypoglycemia associated with insulin use.